2021
DOI: 10.4274/mmj.galenos.2021.36306
|View full text |Cite
|
Sign up to set email alerts
|

The Relation Between the Metopic Suture Persistence and Frontal Sinus Volume and Olfactory Fossa Depth: A Reliability Study with Semiautomatic Volume Measurement

Abstract: Objective: This study aims to investigate the relationship of the persistence of metopic suture (PMS), frontal sinus volume (FSV), and olfactory fossa depth (OFD). Methods: Tomography scans of 1,603 patients aged 18-65 years were evaluated for the presence of PMS. In the study, 74 PMS cases and 74 controls were included. The appearance of each individual’s frontal sinus was classified as aplasia, hypoplasia, or normal. Two observers independently measured the lateral la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(30 reference statements)
0
3
0
Order By: Relevance
“…This observation is consistent with those studies that have argued that complete metopism can affect the presence and/or size of the frontal sinus. As noted above, Guerram et al (2014), Nikolova and Toneva (2019), and Atalay and Eser (2021) recorded small sinuses to be more frequently encountered in individuals with metopism. Kumar et al (2016) reported a relationship between metopism and sinus aplasia, although none of the aplastic crania in the South African sample exhibited metopism.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…This observation is consistent with those studies that have argued that complete metopism can affect the presence and/or size of the frontal sinus. As noted above, Guerram et al (2014), Nikolova and Toneva (2019), and Atalay and Eser (2021) recorded small sinuses to be more frequently encountered in individuals with metopism. Kumar et al (2016) reported a relationship between metopism and sinus aplasia, although none of the aplastic crania in the South African sample exhibited metopism.…”
Section: Discussionmentioning
confidence: 83%
“…At the same time, however, a number of studies have argued that full, or complete metopism can affect the presence and/or size of the frontal sinus (e.g., Rochlin & Rubaschewa, 1934; Torgersen, 1950). Thus, Guerram et al (2014) recorded small frontal sinus size to be more frequently encountered in individuals with metopism, Nikolova and Toneva (2019) described a significant relationship between the presence of a small sinus together with metopism, Atalay and Eser (2021) found metopic individuals to exhibit a 5× higher incidence of sinus hypoplasia, and Kumar et al (2016) reported a relationship between metopism and sinus aplasia. On the other hand, an almost equal number of studies have observed there to be no relationship whatsoever between metopism and frontal sinus size and/or aplasia (e.g., Bilgin et al, 2013; Hunt & Everest, 2001; Marciniak & Nizankowski, 1959; Pondé et al, 2008; Sandre et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation